2019
DOI: 10.4315/0362-028x.jfp-19-066
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Survival in Soil and Transfer Onto Produce via Splash Events

Abstract: Nearly one-half of foodborne illnesses in the United States can be attributed to fresh produce consumption. The preharvest stage of production presents a critical opportunity to prevent produce contamination in the field from contaminating postharvest operations and exposing consumers to foodborne pathogens. One produce-contamination route that is not often explored is the transfer of pathogens in the soil to edible portions of crops via splash water. We report here on the results from multiple field and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Agricultural water used in produce production environments has been identified as a probable route of contamination in past produce outbreaks (Greene et al, 2008;Klontz et al, 2010;Park et al, 2012;Rodrigues et al, 2020). When agricultural water comes into contact with the harvestable portion of a plant during production (e.g., during foliar irrigation, frost protection) or farm environment (e.g., through splash from contaminated soil and feces) fresh produce can become contaminated by human pathogens present in the water (Miles et al, 2009;Erickson et al, 2010;Fatica and Schneider, 2011;Ijabadeniyi et al, 2011;Atwill et al, 2015;Jeamsripong et al, 2019;Lee et al, 2019). Understanding pathogen ecology in freshwater environments used for produce production is critical for ensuring safety and assessing the risk of potential contamination events.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural water used in produce production environments has been identified as a probable route of contamination in past produce outbreaks (Greene et al, 2008;Klontz et al, 2010;Park et al, 2012;Rodrigues et al, 2020). When agricultural water comes into contact with the harvestable portion of a plant during production (e.g., during foliar irrigation, frost protection) or farm environment (e.g., through splash from contaminated soil and feces) fresh produce can become contaminated by human pathogens present in the water (Miles et al, 2009;Erickson et al, 2010;Fatica and Schneider, 2011;Ijabadeniyi et al, 2011;Atwill et al, 2015;Jeamsripong et al, 2019;Lee et al, 2019). Understanding pathogen ecology in freshwater environments used for produce production is critical for ensuring safety and assessing the risk of potential contamination events.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the survival and die-off of attenuated enterohemorrhagic E. coli (EHEC) and nonpathogenic E. coli ( 24 41 ) and Salmonella ( 32 , 35 , 42 ) on in-field leafy greens. For instance, Moyne et al ( 37 ) irrigated in-field lettuce with water contaminated with attenuated E. coli O157:H7 in 3 replicated trials in Salinas, CA, and observed a 2- to 3-log 10 reduction within 2 h of inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…Dust containing antimicrobial residues or ARB can be emitted from livestock units or dried spread manure (Hamscher and Hartung et al, 2008;McEachran Andrew et al, 2015;Schulz et al, 2019) and can therefore represent an additional transmission route. The same holds true for soil particles that can be splashed up onto produce (Lee et al, 2019). Run-off from adjacent, fertilised or grazed fields may also move faecally contaminated soil particles to fresh produce (Barrios et al, 2020).…”
Section: Plant-based Food Production Sectormentioning
confidence: 95%